Secondary English Teachers’ Experiences of Using Information and Communication Technology - Adhikari, Badri Prasad (Journal of NELTA Karnali, 2024)
This study attempts to explore the experiences of English teachers of using ICT and also investigates the digital techniques and tools that the English teachers use in classroom teaching at the community schools of Nepal. This qualitative research evaluated the experience and perception of teachers regarding the use of ICT in this post pandemic (COVID-19) era. The researcher conducted interviews with twenty Secondary Level English teachers on the basis of the guidelines of a set of semi-structured and open-ended questions for data collection and observed their classes visiting the respective school. For the analysis and evaluation of the data obtained from the teachers, phenomenological thematic coding was used. The finding of the study revealed that despite many challenges, teachers use ICT as per the demand of the content and it has been an integral part of modern education system. The findings demonstrated the real picture of the rural community school teachers' condition in terms of the use of ICT. Furthermore, it also paved the way for the concerned authorities and bodies to strengthen the ICT friendly infrastructures of schools.